Pedestrian injuries in school-attending children: a comparison of injury data sources in a low-income setting - Lee, P.P.S.; Rothman, L.; Mutto, M.; Nakitto, M.; Howard, A.W. (Injury prevention, 2009)
To estimate and compare the rate of pedestrian injuries in primary school-attending children of urban Uganda using different data sources.Pedestrian injury rates differed significantly between different data sources. Users must be aware of the different target populations, definitions, and limitations of the data sources before direct comparisons are made. Injury reports by volunteer teachers may be a feasible source of injury data in other low/middle-income countries.
Keywords: Low-income setting; Injury data sources; School-attending children; Pedestrian injuries